2005
DOI: 10.1371/journal.pbio.0030095
|View full text |Cite
|
Sign up to set email alerts
|

Light Controls Growth and Development via a Conserved Pathway in the Fungal Kingdom

Abstract: Light inhibits mating and haploid fruiting of the human fungal pathogen Cryptococcus neoformans, but the mechanisms involved were unknown. Two genes controlling light responses were discovered through candidate gene and insertional mutagenesis approaches. Deletion of candidate genes encoding a predicted opsin or phytochrome had no effect on mating, while strains mutated in the white collar 1 homolog gene BWC1 mated equally well in the light or the dark. The predicted Bwc1 protein shares identity with Neurospor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
270
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(286 citation statements)
references
References 57 publications
12
270
1
3
Order By: Relevance
“…(Image provided by S. Esher and K. Selvig, Duke University.) X. Lin et al Idnurm and Heitman 2005;Brand et al 2007). In contrast, yeasts or yeast-like cells (including conidia, endospores, etc.)…”
Section: Morphotype Niche Adaptation and Fungal Virulencementioning
confidence: 99%
“…(Image provided by S. Esher and K. Selvig, Duke University.) X. Lin et al Idnurm and Heitman 2005;Brand et al 2007). In contrast, yeasts or yeast-like cells (including conidia, endospores, etc.)…”
Section: Morphotype Niche Adaptation and Fungal Virulencementioning
confidence: 99%
“…Some of them have symbiotic associations with plants and algae, while others are used as biocontrol agents against phytopathogenic organisms (Druzhinina & Kubicek, 2005). Further, some groups of fungi are infectious agents and can cause a wide variety of diseases in animals, plants and humans (Idnurm & Heitman, 2005). Consequently, it is of major importance to understand the mechanisms of fungal development and reproduction in order to increase the benefits and decrease the costs that they represent.…”
Section: Introductionmentioning
confidence: 99%
“…WC proteins have been well characterized in the filamentous ascomycete Neurospora crassa (Ballario et al, 1996;Linden and Macino, 1997;Froehlich et al, 2002;He et al, 2002), and homologues have been identified in ascomycetes, basidiomycetes, and zygomycetes (for review, see Corrochano, 2007 (Idnurm and Heitman, 2005;Lu et al, 2005). WHITE COLLAR orthologues are also encoded in the genome of A. nidulans (Greene et al, 2003), and the corresponding gene products have recently been shown to influence light sensing, sexual development, and mycotoxin production (Purschwitz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Phycomyces blakesleeanus mutants defective in blue-light-dependent phototrophism may contain mutations in the madA gene, which encodes a protein similar to WC-1 of N. crassa (Idnurm et al, 2006). Inactivation of a wc-1 homologue in the human pathogen Cryptococcus neoformans results in a blind phenotype (Idnurm and Heitman, 2005;Lu et al, 2005). WHITE COLLAR orthologues are also encoded in the genome of A. nidulans (Greene et al, 2003), and the corresponding gene products have recently been shown to influence light sensing, sexual development, and mycotoxin production (Purschwitz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%